2022
DOI: 10.1177/02611929221098138
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Simulators for Teaching Practical Clinical Skills to Veterinary Students — A Review

Abstract: In the context of veterinary education, simulators are devices or sets of conditions aiming to imitate real patients and enable students to practice skills without the need for live animal use. Simulator use in veterinary education has increased significantly in recent years, allowing consistent practical teaching without reliance on clinical cases. This review examines the available literature regarding the use of simulation and simulators for teaching practical day one competences to veterinary students. Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 81 publications
2
25
0
1
Order By: Relevance
“…The majority of large animal simulators are focused on bovine rectal palpation and/or pregnancy diagnosis [ 11 ], while intrauterine insemination in cows usually requires extensive practice in live animals. One study indicated that in more than 50% of the cases analyzed, the veterinarian was not sufficiently trained to deposit semen in the uterine body, leading to frequent intracervical insemination and, therefore, a decrease in fertility [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of large animal simulators are focused on bovine rectal palpation and/or pregnancy diagnosis [ 11 ], while intrauterine insemination in cows usually requires extensive practice in live animals. One study indicated that in more than 50% of the cases analyzed, the veterinarian was not sufficiently trained to deposit semen in the uterine body, leading to frequent intracervical insemination and, therefore, a decrease in fertility [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study analyzed the results and time of different veterinary simulation techniques showing evident effectiveness in increasing clinical skills with simulator training programs [ 31 ]. Moreover, it is of utmost importance to develop tools such as simulators to help educators to adhere to modern ethical guidelines that aim to protect animal welfare and reduce the need to obtain live animals solely for teaching or pedagogic research purposes [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ein Simulator wird definiert als „device or set of conditions that aims to imitate real patients, anatomic regions, or clinical tasks“. Es handelt sich dabei also um eine Vorrichtung, die darauf abzielt, echte Patienten, anatomische Regionen oder klinische Tätigkeiten zu imitieren 4 . Dabei werden die Handgriffe verschiedenster tierärztlicher Tätigkeiten bei unterschiedlichsten Tierarten und Fächern abgebildet.…”
Section: Wie Funktioniert Ein Skills Lab?unclassified
“…For this issue’s 50th Anniversary Article, Helen Braid has compiled an overview of many of the currently available non-animal alternatives that can be used for teaching practical clinical skills to veterinary students. 7 There are a number of online databases listing these types of non-animal models and simulators, such as those collated by InterNICHE in the UK, as well as a range of educational platforms that provide alternative resources for teaching; some of these are listed in our Resources Round-up section in this issue.…”
mentioning
confidence: 99%